Daidalos at work : a phenomenological approach to the study of Minoan architecture - Palybu, Klairē (INSTAP Academic Press, 2018)
Intro -- Editing -- List of Figures -- List of Abbreviations -- Preface and Acknowledgments -- Introduction -- Architecture and Archaeology: Tasks and Tools -- A Phenomenological Approach -- Managing Absence and Image Making in Archaeology -- Minoan Architecture in the Turmoil of the 20th Century -- The Pioneers -- On Words, Names, and Terms: "Must a Name Mean Something?" -- The Impossible Typology of a Continuum -- Relative Time, Absolute Chronologies -- Land Matters -- The Accident of Location -- The Genius Loci and the Poetics of the Natural Environment -- A Nature Inhabited by Gods, Artists, and Geometers -- The Circle and the Square -- Boundaries and Connectors -- Insulation and Communication -- Bounding Elements -- Connectors -- Hierarchical Circulatory Patterns and the Curse of the Labyrinth -- Configuration of the Constituent Parts -- The Way: Approach and Departure -- Entry and Egress: Crossing the Threshold -- In Between: The Porch -- The Vestibule: An Arriving-Leaving Place -- The Room with the Central Column: Marking the Center -- The Minoan Hall: Symmetry, Order, and Gradation -- The Polythyron Hall: Mutability -- Lustral Basin and Pillar Crypt: Back to the Archetypes -- Storage and Service -- Places with No Names and Tasks out of Place -- Outdoor Spaces -- Design and Execution -- The Commissioner, the Architect, and the Process -- Composition and Design Tools -- The Quantitative Aspect of Architecture -- The Art of Building -- Building as Technology -- Building Materials -- Structural Systems: Massive versus Skeleton -- Multistory Construction -- Standardization (and Prefabrication?) -- Responding to Seismic Threat -- The Art of Appearance -- Undulating Ground, Indented Facades, Stepped Skyline -- Solids and Voids -- Ordering Principles -- The Elusive Effect of Symmetry -- Ornament: The Art of Display and Concealment